(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Early identification of severe acute pancreatitis is of paramount importance in the management and for improving outcomes. Bedside index for severity in acute pancreatitis (BISAP) is a simple and accurate score for stratification in acute pancreatitis. This study was conducted to find out the accuracy of BISAP score in predicting outcomes of acute pancreatitis in local population. Method: We prospectively analyzed 96 patients with acute pancreatitis from February 2019 to December 2019. Revised Atlanta classification was used to stratify mild, moderately severe and severe pancreatitis. BISAP score was calculated within 24 hours of admission. Accuracy was measured by area under receiver operating curve (AUC). Result: Out of 96 patients, alcohol related acute pancreatitis accounted for 74.7%. There were 63.2% of mild AP, 37.3% of moderately severe AP, 9.4% of severe AP and 15.8 % of pancreatic necrosis. The AUC for moderately severe AP, severe AP and pancreatic necrosis were 0.77 (CI 0.68-0.87), 0.95 (CI 0.90-0.99) and 0.87 (CI 0.79-0.96) respectively. The statistically significant BISAP cut off for diagnosing sever AP was≥3, and ≥2 for moderately sever AP and pancreatic necrosis. There was positive correlation between revised Atlanta severity of acute pancreatitis and length of hospital stay (r=0.41). Mortality was 3.3 % which was seen in BISAP score 3 or above. Conclusion: BISAP is a simple predictive model in identifying patient at a risk of developing different severity of pancreatitis and its outcome in our population.